The Relationship of Phytoplankton Primary Productivity Values with Physical and Chemical Factors in Parapat Waters, Lake Toba - erna ningsih (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2022)
The aimed of this research were to investigate the relation of primary productivity value with the chemistry physic factor Parapat, Lake Toba. Primary productivity in Lake Toba from activity photosynthesis of done by chlorophyl. This research has been done during March 2009 at 3 sampling location around Parapat, Lake Toba. The locations research obtained base on variation activity to obtained location research.  Primary productivity was measured by the Oxygen Method were two bottles with a given conceration of phytoplankton (small aqutac organism) are suspended at the depth from wich the samples were obtained. The “dark” bottle is wrapped in aluminium foil to exclude light: “light” bottle is clear. A quantity of oxygen proportional to the total organic matter fixed (gross production) is produced by photosynthesis in the light bottle. At the same time, some of oxygen is being utilized in respiration. The other analysis would be conducted to measurement such as temperature, pH, DO, BOD, COD, nitrat, fospat, chlorophyl a, abundant phytoplankton, light penetration, light intensity. The value of primary productivity range from 112,608-825,792 mgC/m3/day and with the highest value of primary productivity equal to 825,792 mgC/m3/day obtained at the depth 7 m (station I), the value of chlorophyl equal to 62,013 mg/m3 obtained at the surface (station III) and the lowest value of chlorophyl a equal to o,801 mg/m3 obtained at the depth 3,5 m (station III), beside the value of phytoplankton equal to 3306,12 ind/l obtained at the depth surface (station I) and the value of phytoplankton equal to 1469,39 ind/. According to statistical the test obtained that there no significance difference of value of primary productivity which is compared between station or depth.